CONCEPTION OF DEVELOPMENT OF THE STATE INTERNATIONAL AIRPORT BORYSPIL - Veruzhsky, Y.V.; Rodchenko, O.V.; Sologub, O.V. (Proceedings of National Aviation University (archive), 2005)
Analysis of existing concepual variants of development of the State Boryspil International Airport and new conception variant with prognosis of economic efficiency is presented.